Identification of drugs and drug metabolites as substrates of multidrug resistance protein 2 (MRP2) using triple-transfected MDCK-OATP1B1-UGT1A1-MRP2 cells - Fahrmayr, C (Blackwell Publishing Ltd, 2012)
BACKGROUND AND PURPOSE: The coordinate activity of hepatic uptake transporters [e.g. organic anion transporting polypeptide 1B1 (OATP1B1)], drug-metabolizing enzymes [e.g. UDP-glucuronosyltransferase 1A1 (UGT1A1)] and efflux pumps (e.g. MRP2) is a crucial determinant of drug disposition. However, limited data are available on transport of drugs (e.g. ezetimibe, etoposide) and their glucuronidated metabolites by human MRP2 in intact cell systems. EXPERIMENTAL APPROACH: Using monolayers of newly established triple-transfected MDCK-OATP1B1-UGT1A1-MRP2 cells as well as MDCK control cells, single- (OATP1B1) and double-transfected (OATP1B1-UGT1A1, OATP1B1-MRP2) MDCK cells, we therefore studied intracellular concentrations and transcellular transport after administration of ezetimibe or etoposide to the basal compartment. KEY RESULTS: Intracellular accumulation of ezetimibe was significantly lower in MDCK-OATP1B1-UGT1A1-MRP2 triple-transfected cells compared with all other cell lines. Considerably higher amounts of ezetimibe glucuronide were found in the apical compartment of MDCK-OATP1B1-UGT1A1-MRP2 monolayers compared with all other cell lines. Using HEK cells, etoposide was identified as a substrate of OATP1B1. Intracellular concentrations of etoposide equivalents (i.e. parent compound plus metabolites) were affected only to a minor extent by the absence or presence of OATP1B1/UGT1A1/MRP2. In contrast, apical accumulation of etoposide equivalents was significantly higher in monolayers of both cell lines expressing MRP2 (MDCK-OATP1B1-MRP2, MDCK-OATP1B1-UGT1A1-MRP2) compared with the single-transfected (OATP1B1) and the control cell line. CONCLUSIONS AND IMPLICATIONS: Ezetimibe glucuronide is a substrate of human MRP2. Moreover, etoposide and possibly also its glucuronide are substrates of MRP2. These data demonstrate the functional interplay between transporter-mediated uptake, phase II metabolism and export by hepatic proteins involved in drug disposition.